Human resource development in twentieth-century Japan nijisseiki Nihon no jinteki shigen / chosha Inoki Takenori ; yakusha Tonī Gonzaresu. - Inoki, Takenori (Japan library (Shuppan Bunka Sangyō Shinkō Zaidan), 2017)
"In this book, we will examine the formation and allocation of human resources that brought about economic growth, focusing on the form of education and training in schools, companies, and the military. In particular, how are knowledge and skills delivered in a 'have-not' country like Japan? Following transitions form the Edo period to the present age, we approach the core of Japanese systems from both historical and theoretical perspectives"--Back cover.